Fabrication and Optimization of Various Superdisintegrants to Formulate Zolpidem Tartarate Fast Dissolving Tablets - Srikanth Choudary Pallothu; Nellutla Sandeepthi; N.Sriram (International Journal of Pharmacy and Analytical Research, 2022)
In the general perspective, oral administration is the most popular route about 50-60% of total dosage forms are administered due to ease of ingestion, pain avoidance, versatility (to accommodate various types of drug candidates), and most importantly patient compliance. Difficulty in swallowing is also a common problem of all groups, especially the elderly and pediatrics, because of physiological changes associated with these groups. Taste of a pharmaceutical product is an important parameter governing compliance. Hence this research angled to extend towards the selection and optimization of superdisintegrants to formulate Zolpidem Tartarate fast dissolving tablets by direct compression method. The formulations F13, F14, 15 and F16 which contained increasing concentrations of combination of cross povidone with cross Croscarmellose sodium have recorded drug release 94.5%, 96.52%,99.87% and 96.38% respectively, at the end of 25 to 30 min. From the result it has been revealed that, the disintegration and dissolution of the formulation F15 contained cross povidone (5%) with cross Croscarmellose sodium (5%) was the best formulation among the all other formulations. Consequently, the formulation of the selected drug has been successfully developed as fast dissolving tablets which might significantly improve the patient compliance.